Ekspansi Kelompok Usaha Batik Daerah: Desa Klakah Kabupaten Lumajang - Ninik Lukiana; Kasno T Kasim; Noviansya Rizal (IMPOWERMENT SOCIETY, 2017)
Small industrial of batik "SEKAR SARI" and "SUMBER AGUNG" is a small industry develop business the batik area which has a special design motif that accentuates their regional, has a special characteristic on the motif, such as a banana image, banana shoots, mountain and dance horse. Ipteks activities for the community of training technology, design batik, provided assistance in establishing a permanent means of drying space batik, provided assistance in establishing of infrastructure the place pelorodan/sink batik, disposal waste pelorodan, providing training and assistance in the management of marketing and simple accounting. Training results obtained special design that characterizes the batik District Klakah, obtained ways of the making batik is more efficient with using staining remasol and the use of tool of the form bidangan of the of bamboo. The Making a place permanent pelorodan by placing filtering, so that waste water is wasted just a coloration secondhand. The wax Waste filtered which next can still be used again. The water Waste flows in place the form disposal a filtering so it does not get the river and do not pollute the environment, location, drying is not directly exposed to sunlight will produce a more perfect batik coloring.